2017
DOI: 10.1152/ajpheart.00617.2016
|View full text |Cite|
|
Sign up to set email alerts
|

Prediction of hemodynamics under left ventricular assist device

Abstract: Hemodynamic response to left ventricular assist device (LVAD) has not been quantitatively investigated. This is the first report of quantitative prediction of the hemodynamics on LVAD using circulatory equilibrium framework. The validated framework allows us to simulate the impact of LVAD on right atrial pressure under various right ventricular functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
(29 reference statements)
2
10
0
Order By: Relevance
“…Once we established the model using haemodynamic parameters in a given condition, we could predict haemodynamics under various conditions such as myocardial infarction, blood volume gain and/or loss, extra-corporeal membrane oxygenation, and left ventricular assist device. [12][13][14] The results of this study also support the robustness of generalized circulatory equilibrium. Except for severe HF, Q S hardly decreases because the oxygen demand of the whole body determines Q S .…”
Section: Prediction Of Interatrial Shunting Haemodynamics By Generalisupporting
confidence: 76%
See 2 more Smart Citations
“…Once we established the model using haemodynamic parameters in a given condition, we could predict haemodynamics under various conditions such as myocardial infarction, blood volume gain and/or loss, extra-corporeal membrane oxygenation, and left ventricular assist device. [12][13][14] The results of this study also support the robustness of generalized circulatory equilibrium. Except for severe HF, Q S hardly decreases because the oxygen demand of the whole body determines Q S .…”
Section: Prediction Of Interatrial Shunting Haemodynamics By Generalisupporting
confidence: 76%
“…In this study, we set F R = 2.13, H R = 1.9, and RVEF e = 0.6 for normal RV function, and R-P = 0.1 mmHg/mL/min/kg for normal pulmonary circulation as reported previously. 12,14,15 We previously reported that in a distributed resistance-compliance vascular model, the following equations represent the stressed blood volume of the systemic circulation and pulmonary circulation 11 :…”
Section: Theoretical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, acute pulmonary edema upon initiation of VA-ECMO has been described ( 35 ). In such patients, it may be beneficial to consider left atrial decompression (balloon atrial septostomy or placement of a new left atrial cannula) or transitioning to ventricular assist device [VAD] rather than ECMO ( 36 ).…”
Section: Overview Of Ecmo and Important Physiological And Hemodynamicmentioning
confidence: 99%
“…These contrasting views have not been reconciled in a subsequent theoretical debate (2,9,28). The control of VR is highly relevant in clinical treatment of circulatory failure, especially in the widespread use of modern circulatory assist devices (24).…”
mentioning
confidence: 99%